Preferences for and drivers of adult vaccination clinic site selection: A cross-sectional study in 30 provinces in China - Yuxi Liu; Yanlin Cao; Yugang Li; Siyuan Liu; Yunshao Xu; Weizhong Yang; Luzhao Feng (Human Vaccines & Immunotherapeutics)
Focusing on vaccines available to adults and not in the immunization schedule, this study investigates the preferences and factors influencing adults in selecting vaccination clinic locations. It aims to provide strategic insights for boosting vaccination rates by analyzing adults’ decision-making factors. This contributes to developing more efficient, patient-focused vaccination strategies that tackle vaccine hesitancy and improve access to vaccination sites. We conducted a cross-sectional study through the “YueMiao” platform from November 1 to December 10, 2023, using convenience and purposive sampling to engage 2014 participants. We collected data via online surveys that included questions about sociodemographic characteristics, sources of vaccination clinic information, clinic satisfaction, and the impact of site selection on vaccination decisions. Our findings reveal that adults’ site preferences for vaccination are influenced by gender, age, income, and vaccination history. Participants showed a strong preference for locations that offer convenience, efficiency, transparent pricing, and a comfortable environment. Analysis of service satisfaction at these clinics indicates that vaccinated individuals report higher satisfaction with appointment systems, wait times, and service hours than those unvaccinated. Furthermore, the preference for vaccination sites consistently aligns with the vaccine type, with a majority opting for community health service centers. Our results suggest that public health strategies should concentrate on enhancing site convenience, service quality, and information transparency to elevate adult vaccination rates. Future initiatives should aim to increase public trust in vaccines, improve the selection and quality of vaccination sites, and effectively utilize digital technology for spreading vaccination information.